Expository Learning Strategy in Instilling Moral Values and Religious Life in Grade VI Students at Sd Negeri 09 Cilincing - Zauhar Roziqin; Khalid Ramdhani; Maskur Mansyur (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to examine the effectiveness of expository learning strategies in instilling moral values and religious life in grade VI students. The research method used is descriptive qualitative research with data collection techniques through observation, interviews, and documentation. The results showed that the expository learning strategy was able to gradually increase students' religious awareness. During three meetings, the indicators of learners' religious awareness showed an increase, especially in the aspect of applying moral values and religious life. Teachers have an important role in delivering material in a clear and structured manner, as well as providing concrete examples relevant to everyday life. However, some indicators such as students' awareness and ability to read the Qur'an, awareness of doing assignments honestly, and the ability to give conclusions from the subject matter did not increase or tended to be monotonous. Based on the results of the research and discussion, it can be concluded that overall, the expository learning strategy carried out by educators can increase religious awareness and instill moral values for students gradually. Disciplinary rules applied at school, moral learning both inside and outside the classroom, and educators who are role models make a significant contribution. However, there are some aspects that need further attention, such as awareness of reading the Qur'an and honesty in doing assignments.The recommendation from this study is that teachers continue to develop skills in using expository strategies and create a conducive learning environment to support the achievement of character education goals.